EMarketing: The essential guide to online marketing - Stokes, Rob (Quirk eMarketing, 2016)
Marketing is about conversations, and the Internet has become a hub of conversations. The connected nature of the Internet allows us to follow and track these conversations, and provides entry points for all parties. What follows in this book are ways of conversing with potential and existing customers using the Internet.